Spontaneous Retroperitoneal Hematoma Simulating Ruptured Infrarenal Aortic Aneurysm in a Patient with End-Stage Renal Disease - Li, JYY; Chan, YC; Qing, KX; Cheng, SW (International Journal of Angiology, 2016)
We reported a case of spontaneous retroperitoneal hematoma (SRH) simulating a ruptured infrarenal aortic aneurysm. A 72-year-old man with a history of infrarenal aortic aneurysm and end-stage renal disease on hemodialysis presented with malaise and nonspecific central abdominal pain and left loin discomfort. An emergency computed tomography scan showed a large retroperitoneal hematoma and clinical suspicion of ruptured infrarenal aortic aneurysm. However, the hematoma was discontinuous with the aneurysm sac and raised the clinical suspicion on dual pathology. The SRH was treated conservatively with transfusion of blood products, and the aneurysm was treated with nonemergency endovascular repair electively. This case demonstrates the importance of recognizing different clinical and radiological characteristics and be aware of dual pathology.
Keywords: spontaneous retroperitoneal hemorrhage; hematoma; infrarenal aortic aneurysm; ecchymosis; hemodialysis